1997
DOI: 10.1046/j.1365-2168.1997.02846.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid plaque characteristics and presenting symptom

Abstract: There was an association between echolucent type I and II carotid plaques and the presence of symptoms but not their type. Plaque morphology was not characteristic in a subgroup of patients who had stroke without warning. Further prospective study of plaque morphology in asymptomatic patients might help identify high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
2
37
1
1
Order By: Relevance
“…[1][2][3] Few studies have quantified the association between carotid plaques and risk of subsequent stroke in asymptomatic subjects. 4,5 Also, limited information is available on the relationship with subtypes of cerebral infarction 4,5 as well as on the impact of location of the carotid plaque in relation to the risk of stroke.…”
mentioning
confidence: 99%
“…[1][2][3] Few studies have quantified the association between carotid plaques and risk of subsequent stroke in asymptomatic subjects. 4,5 Also, limited information is available on the relationship with subtypes of cerebral infarction 4,5 as well as on the impact of location of the carotid plaque in relation to the risk of stroke.…”
mentioning
confidence: 99%
“…7) Plaque morphology is another factor associated with increased risk of stroke. 1,2,6) For example, echolucent plaque is significantly more common in symptomatic patients than in asymptomatic patients. 6) Other studies have also suggested an association between echolucent plaque and the subsequent development of neurologic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,6) For example, echolucent plaque is significantly more common in symptomatic patients than in asymptomatic patients. 6) Other studies have also suggested an association between echolucent plaque and the subsequent development of neurologic symptoms. 1,2) In the present patients, preoperative cerebral angiography and carotid echography revealed ulceration and echolucent plaque in the affected carotid artery, which was confirmed by postoperative macroscopic examination findings of ulcerated plaque with thrombi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations